DEVELOPMENT OF SMARTPHONE WASTE MANAGEMENT PLATFORM USING DESIGN THINKING APPROACH TO SUPPORT IMPLEMENTATION OF EXTENDED PRODUCER RESPONSIBILITY (EPR) IN INDONESIA'S SMARTPHONE INDUSTRY - Farid Akbar Harahap; Rina Djunita Pasaribu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Indonesia generated approximately 1.9 million tons of electronic waste (e-waste) in 2021, growing at an annual rate of 39%. By 2030, e-waste generation is projected to reach 4.4 million tons. A study by the National Development Planning Agency (Bappenas) revealed that only 17.4% of e-waste was recycled in 2021, highlighting the inefficiency of Indonesia's current e-waste management system. Smartphones are the most frequently disposed of e-waste, with an average lifespan of 3.42 years—shorter than most electronic devices. By 2028, over 40 million discarded smartphones are expected to significantly contribute to e-waste. To address this, the Indonesian government introduced a circular economy roadmap through Regulation No. 75 of 2019, mandating Extended Producer Responsibility (EPR). However, its implementation has been suboptimal, hindered by limited collaboration among stakeholders. Effective smartphone waste management requires awareness, clear procedures, secure data handling, and practices that maximize economic value. This study involves key stakeholders—consumers, producers, waste managers, and government representatives—to co-design solutions using a design thinking approach. The research delivers a smartphone waste management prototype, comprising a service blueprint and a high-fidelity platform, to support value exchange and improve EPR implementation in the smartphone industry.